التناص وجمالياته في ديوان أوراق لاتنحنى للشاعر "ابو بكر مراد" - حسيني، فتيحة; بن خدوجه، جمال; حمده، سالم; دوش، عبد الحميد (University of Eloued جامعة الوادي, 2024)
يقف بحثنا عند الظاهرة النقدية "التناص" من منطلق بروزه ضمن مناهج ما بعد الحداثة والإقبال الشديد الذي شهده من طرف نقادها؛ إيمانا منهم بدوره في تشكيل النص الأدبي بالنسبة للمبدع وكذلك في توجيه المتلقي نحو دراسة وفهم هذا النص الأدبي. وإيمانا منا بتَمَظْهُر التناص ضمن النصوص الأدبية مهما اختلفت شكلا وزمانا ومكانا؛ جاءت دراستنا لتسلط الضوء على هذه الظاهرة ضمن ديوان الشاعر أبو بكر مراد المعنون:" أوراق لا تنحني"؛ منطلقين من كون الأفكار والنصوص تتراكم عبر الزمن من خلال ثقافة المبدع وتواصله الاجتماعي وكذلك من خلال مساره الدراسي والمهني والإبداعي، مما يشكل ثروة وطاقة موجهة لإنتاجه الإبداعي، الذي يتعالق بصفة إرادية أو غير إرادية مع تلك النصوص المتراكمة مما يفتح نصوصه الجديدة على تأويلات مختلفة تزيد في جمالياتها وتتيح للمتلقي تذوقها بعيدا عن دائرة الانغلاق والمحلية. Our research focuses on the critical phenomenon of “intertextuality ” based on its emergence within postmodernist curricula and the strong demand it has witnessed from its critics. Out of their belief in its role in forming the literary text for the creator, as well as in directing the recipient towards studying and understanding this type of text. In our belief about the use of intersexuality within literary texts, regardless of their form, time, and place; Our study came to shed light on this phenomenon within the poetry collection of the poet Abu BakrMurad entitled: “papers That Do Not Bend.” Based on the fact that ideas and texts accumulate over time through the creator’s culture and social communication, as well as through his academic, professional and creative path, which constitutes wealth and energy directed to his creative production, which is voluntarily or involuntarily linked to those accumulated texts, which opens up his texts to different interpretations that increase its aesthetics and allow the recipient to taste it away from the closing circle and localism.
811/ 005
Keywords: التناص، الجملية، أوراق لا تنحني، أبو بكر مراد; Intertextuality; The Sentence; Leaves That Do Not Bend; Abu Bakr Murad.